Identification of compounds from the Illicium extract / Fadzilah Haris, Hannis Fadzillah Mohsin and Ibtisam Abdul Wahab - Haris, Fadzilah; Mohsin, Hannis Fadzillah; Abdul Wahab, Ibtisam (Universiti Teknologi MARA Cawangan Pulau Pinang, 2018)
This study is to highlight the various uses/benefits of star anise (Illicium species). It is regarded as the sole genus from the Illiciaceae, which originated from the Schisandraceae family. This plant is known as “bunga lawang” among the Malays. It has long been used in traditional Chinese medicine. The medicinal properties of the star anise include it being antimicrobial and antiviral. Previous publication mentioned on the anticancer attributes of Illicium’s essential oils against colon cancer. The star anise also can be used as an antiviral agent that led to the existence of drug, Tamiflu®. The objectives of this research are to review the Illicium genus and to report the separation of the compounds from the star anise seed. Standard analytical chemistry methods and high-field nuclear magnetic resonance spectroscopic techniques were utilized in order to identify the secondary metabolites. From the literatures, the isolation of natural biomolecules from Illicium species could be achieved by using simultaneous distillationextraction and solid phase microextraction. Furthermore, the determination of volatile compounds could be accomplished via gas chromatography-mass spectrometry. Shikimic acid is also the target compound to be extracted, due to its role in the antiviral synthesis. The non-volatile component could be obtained from liquid chromatography. Finally, it is found that mixtures of trans-anethole, anisaldehyde and a triglyceride could be detected from the seed extract.